Effect of Temperature and Humidity on Oil Quality of Harvested Torreya grandis cv. Merrillii Nuts During the After-Ripening Stage - Zhang, Zuying; Jin, Hangbiao; Suo, Jinwei; Yu, Weiyu; Zhou, Minyin; Dai, Wensheng; Song, Lili; Hu, Yuanyuan; Wu, Jiasheng (Frontiers in Plant Science, 2020)
Temperature and relative humidity (RH) influence post-harvest ripening, a crucial stage for quality promotion in some oil plants or fruits. Torreya grandis (T. grandis) nuts, which are rich in unsaturated fatty acids, are easily affected by temperature and humidity conditions during the post-harvest ripening stage and oxidize quickly, leading to deterioration of nut quality. In this study, the main nutraceutical components, fatty acid composition, and related metabolic parameters of lipid rancidity under four treatments (20°C and 70% RH, T20-LH; at 30°C and 70% RH, T30-LH; at 20°C and 90% RH, T20-HH; at 30°C and 90% RH) were measured. Advancement of post-ripening process was quantified under the HH treatments (T20-HH and T30-HH) compared to the LH treatments, as indicated by shorter time of the seed coat complete darken and much more reduction in starch content. The amount of unsaturated fatty acids (UFA) significantly decreased under T30-HH from 12 to 16 d of ripening time, but significantly increased under T20-HH. The acid value (AV) and lipase activity under T30-HH remained virtually constant from 12 to 16 d of ripening time, and this was accompanied by a dramatic increase in POV, LOX activity, and relative expression of the LOX2 gene. Meanwhile, a significant positive correlation between LOX activity and peroxide value (POV), MDA content, and O2·- content was observed. The results imply that the lower amount of oxidative rancidity induced by T20-HH during the late after-ripening stage is related to the LOX activity induced by down-regulation of the LOX2 gene. Therefore, the T20-HH treatment was not only able to promote the post-harvest process of T. grandis ‘Merrillii’ nuts but also slow oxidation of lipids, which ultimately was associated with better oil quality at the late after-ripening stage.